137Cs contamination in the Adamello glacier: Improving the analytical method. (November 2019) - Di Stefano, Elena; Clemenza, Massimiliano; Baccolo, Giovanni; Delmonte, Barbara; Maggi, Valter
Abstract: An alpine ice core, extracted from the Adamello glacier (Central Italian Alps), was analyzed in its entire length through low background γ -spectroscopy, for the detection of 137 Cs. Our results show that in glacier ice 137 Cs is tightly bound to insoluble particulate matter inside the ice core, and it is therefore possible to restrict γ -spectroscopy analysis to particulate matter only. We show how the sensibility of the detection limit can be improved by almost one order of magnitude by using a well-type detector instead of a coaxial one. Hypothesis on the dating of some radioactive layers are also hereby presented. Highlights: 137 Cs is mostly bound to particulate matter inside ice cores. Despite being a temperate glacier, it is possible to construct a profile of the Adamello ice core. The Adamello glacier is subjected to local contamination of 137 Cs coming from the surrounding area.